The Specific Elongation Factor to Selenocysteine Incorporation in Escherichia coli: Unique tRNASec Recognition and its Interactions - Serrão, Vitor Hugo Balasco; Fernandes, Adriano de Freitas; Basso, Luis Guilherme Mansor; Scortecci, Jéssica Fernandes; Crusca Júnior, Edson [UNESP]; Cornélio, Marinônio Lopes [UNESP]; de Souza, Bibiana Monson [UNESP]; Palma, Mário Sérgio [UNESP]; de Oliveira Neto, Mario [UNESP]; Thiemann, Otavio Henrique (Elsevier, 2021)
Several molecular mechanisms are involved in the genetic code interpretation during translation, as codon degeneration for the incorporation of rare amino acids. One mechanism that stands out is selenocysteine (Sec), which requires a specific biosynthesis and incorporation pathway. In Bacteria, the Sec biosynthesis pathway has unique features compared with the eukaryote pathway as Ser to Sec conversion mechanism is accomplished by a homodecameric enzyme (selenocysteine synthase, SelA) followed by the action of an elongation factor (SelB) responsible for delivering the mature Sec-tRNASec into the ribosome by the interaction with the Selenocysteine Insertion Sequence (SECIS). Besides this mechanism being already described, the sequential events for Sec-tRNASec and SECIS specific recognition remain unclear. In this study, we determined the order of events of the interactions between the proteins and RNAs involved in Sec incorporation. Dissociation constants between SelB and the native as well as unacylated-tRNASec variants demonstrated that the acceptor stem and variable arm are essential for SelB recognition. Moreover, our data support the sequence of molecular events where GTP-activated SelB strongly interacts with SelA.tRNASec. Subsequently, SelB.GTP.tRNASec recognizes the mRNA SECIS to deliver the tRNASec to the ribosome. SelB in complex with its specific RNAs were examined using Hydrogen/Deuterium exchange mapping that allowed the determination of the molecular envelopes and its secondary structural variations during the complex assembly. Our results demonstrate the ordering of events in Sec incorporation and contribute to the full comprehension of the tRNASec role in the Sec amino acid biosynthesis, as well as extending the knowledge of synthetic biology and the expansion of the genetic code.
Keywords: elongation factor; SelB; selenocysteine; tRNA[Ser]Sec, protein-RNA interaction